Enhancing streamflow forecasting using the augmenting ensemble procedure coupled machine learning models: case study of Aswan High Dam - Rezaie-Balf, Mohammad; Naganna, Sujay Raghavendra; Kisi, Ozgur; El-Shafie, Ahmed (Taylor & Francis, 2019)
The potential of the most recent pre-processing tool, namely, complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN), is examined for providing AI models (artificial neural network, ANN; M5-model tree, M5-MT; and multivariate adaptive regression spline, MARS) with more informative input–output data and, thence, evaluate their forecasting accuracy. A 130-year inflow dataset for Aswan High Dam, Egypt, is considered for training, validating and testing the proposed models to forecast the reservoir inflow up to six months ahead. The results show that, after the pre-processing analysis, there is a significant enhancement in the forecasting accuracy. The MARS model combined with CEEMDAN gave superior performance compared to the other models–CEEMDAN-ANN and CEEMDAN-M5-MT–with an increase in accuracy of, respectively, about 13–25% and 6–20% in terms of the root mean square error. © 2019, © 2019 IAHS.